2020
DOI: 10.3390/toxins12120735
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Efficiency of Hydroxycinnamic Acids to Inhibit the Production of Enniatins by Fusarium avenaceum and Modulate the Expression of Enniatins Biosynthetic Genes

Abstract: Enniatins (ENNs) that belong to the group of emerging mycotoxins are widespread contaminants of agricultural commodities. There is currently insufficient evidence to rule out health concerns associated with long-term exposure to ENNs and efforts must be strengthened to define a control strategy. While the potential of plant compounds to counteract the contamination with legislated mycotoxins has been reported, little remains known regarding ENNs. The present study evidenced for the first time the efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The volatiles compounds from two amounts of EOs inhibiting 22 and 73% of the mycelial growth and decreased the concentration of ENNs by 67 and 80%, respectively. Hydroxycinnamic acids were shown to interfere with both the growth of F. avenaceum and its production of ENNs [52]. However, in certain situations, a significant reduction in ENNs yield and a drastic transcriptional down-regulation of two genes involved in ENNs biosynthesis were observed while F. avenaceum growth was not or weakly affected, corroborating the occurrence of a regulatory mechanism that specifically targeted the production of ENNs [52].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The volatiles compounds from two amounts of EOs inhibiting 22 and 73% of the mycelial growth and decreased the concentration of ENNs by 67 and 80%, respectively. Hydroxycinnamic acids were shown to interfere with both the growth of F. avenaceum and its production of ENNs [52]. However, in certain situations, a significant reduction in ENNs yield and a drastic transcriptional down-regulation of two genes involved in ENNs biosynthesis were observed while F. avenaceum growth was not or weakly affected, corroborating the occurrence of a regulatory mechanism that specifically targeted the production of ENNs [52].…”
Section: Discussionmentioning
confidence: 73%
“…Hydroxycinnamic acids were shown to interfere with both the growth of F. avenaceum and its production of ENNs [52]. However, in certain situations, a significant reduction in ENNs yield and a drastic transcriptional down-regulation of two genes involved in ENNs biosynthesis were observed while F. avenaceum growth was not or weakly affected, corroborating the occurrence of a regulatory mechanism that specifically targeted the production of ENNs [52]. With A. pusilla EO also, the antifungal and antimycotoxigenic activities could be partly the results of independent regulation mechanisms that need to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Koh et al [ 41 ] have reported that pterostilbene (two methoxyl and one hydroxyl groups), but not resveratrol (three hydroxyl groups), detained potent fungicidal and sporicidal activities against Leptosphaeria maculans and could protect canola seedlings from blackleg infection. Recent studies, dealing with the efficiency of hydroxycinnamic acids to inhibit fungal growth and toxin biosynthesis by Fusarium avenaceum, Aspergillus westerdijkiae and Penicillium verrucosum , supported the key importance of methoxyl groups [ 42 , 43 ]. Since it is widely acknowledged that substitution with methoxyl groups contributes to the lipophilicity of a compound, we can suppose that the predominance of mono- and di-methylated phenolics in the maritime pine 175 °C extract partially explains its high efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The previous authors indicated that the lowest toxicity of coumaric and caffeic acids (one and two hydroxyl groups, respectively) could be related to their capacity to induce the expression of fungal genes encoding phenolic acid degrading enzymes. Besides, the afore published studies suggested that the inhibition of the trichothecene and enniatin mycotoxin production by ferulic acid could be explained by the reduction of the expression of some key biosynthetic genes suggesting the occurrence of a transcriptional control exerted by phenolic acid [ 9 , 11 , 42 ].…”
Section: Discussionmentioning
confidence: 99%